2010
DOI: 10.1007/s13312-010-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral zinc supplementation on the growth of preterm infants

Abstract: Zinc supplementation for preterm low birth weight babies is found effective to enhance the growth in early months of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 12 publications
(19 reference statements)
3
36
2
1
Order By: Relevance
“…Islam et al 5 in a trial of Zn supplementation in 100 PT LBW infants for 6 weeks (2 mg/kg) found significant effect on weight as well as on length but the effect on HC was not significant in his study. Hoque et al 11 in 2005 in a study of 200 LBW infants also found significant effect of Zn supplementation on weight gain.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Islam et al 5 in a trial of Zn supplementation in 100 PT LBW infants for 6 weeks (2 mg/kg) found significant effect on weight as well as on length but the effect on HC was not significant in his study. Hoque et al 11 in 2005 in a study of 200 LBW infants also found significant effect of Zn supplementation on weight gain.…”
Section: Discussionmentioning
confidence: 77%
“…No serious adverse effect was noted related to supplementation therapy 5 . Zinc deficiency in infants has been shown to have an adverse impact on growth and immunity in many studies 2 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Autorzy badań sugerują, że w takim przypadku wskazane jest stosowanie cynku w dawce około 10 mg na dobę. Należy jednak zaznaczyć, że równolegle powinna być stosowana suplementacja innych minerałów (głównie miedzi i żelaza), gdyż zwiększona podaż cynku może prowadzić do ich niedoboru [47,48]. Kolejnym wskazaniem do wprowadzenia suplementacji cynku jest ostra biegunka występująca u noworodków, niemowląt i dzieci w wielu krajach rozwijają-cych się.…”
Section: Suplementacja Preparatami Cynkuunclassified
“…In this issue of Indian Pediatrics, Islam and colleagues report the findings of a double blind randomized controlled trial evaluating the efficacy of oral zinc supplementation on the growth of hospital born preterm infants in the Neonatal Special Care Unit of Dhaka in Bangladesh (2). This is the first study carried out selectively among preterm babies to evaluate the effect of zinc supplementation in a developing country setting.…”
Section: E D I T O R I a L E D I T O R I A L E D I T O R I A L E D I mentioning
confidence: 99%